Edukasi Elisitor Pupuk Biosaka di Desa Semingkir Kecamatan Randudongkal Pemalang - Putranto, Nugroho Dwi; Priyanto, Aris (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
This research is motivated by agricultural problems in Semingkir village, where the farming community experiences a lack of subsidized fertilizer purchase costs, so other alternatives are needed in organic fertilizers. So Biosaka becomes one of the alternatives chosen by the KKN Batch 56 group at the 69 State Islamic University, KH. Abdurrahman Wahid Pekalongan. The purpose of this Biosaka fertilizer-making training is to maximize agricultural land's fertilization level and reduce the cost of agricultural fertilizers. This activity is carried out in the form of observation and training with the target community of the farming community within the scope of Semingkir village. This Biosaka fertilizer-making training activity found that the farming community had the ability and knowledge of Biosaka elicitors and was very enthusiastic about carrying out the practice of making Biosaka fertilizer.